Nationwide Study of Neuropsychiatric Comorbidity and Medicines Use in Children With Autism Spectrum Disorder in Norway - Kiselev, Yury; Handal, Marte; Hjellvik, Vidar; Reichborn-Kjennerud, Ted; Stoltenberg, Camilla; Suren, Pål; Havdahl, Alexandra; Skurtveit, Svetlana (Frontiers in Psychiatry, 2020)
Purpose: Autism spectrum disorder (ASD) has a high rate of comorbidity. While many children with ASD are exposed to psychotropic medicines, their efficacy and safety in these patients are unclear. There is a need for more detailed knowledge on which medicines are most commonly used and for which disorders. We aimed to investigate (a) prevalence and incidence rate of ASD among Norwegian children, and further, among newly diagnosed ASD children in 2014, study the (b) co-occurrence of neuropsychiatric disorders, (c) use of psychotropic drugs, and (d) the relationship between co-occurring diagnoses and use of psychotropic drugs. Method: Nationwide registry-based study of children 2–17 years old in Norway. Results: The ASD prevalence was 0.76% and the incidence rate was 0.12% in 2014. Of the children who received an initial ASD diagnosis in 2014 (n = 1,234), 64.8% had one or more co-occurring neuropsychiatric diagnosis. Psychotropic medication use was moderate ( 20% used stimulants or hypnotics) in general, and low in children without comorbidity (nearly only hypnotics). There was a good accordance between co-occurring diagnoses and indication for the prescribed medications. Conclusions: Children with newly diagnosed ASD mainly received psychotropic drugs to treat co-occurring neuropsychiatric conditions.